Evaluation on accessibility of Information and Communication Technology (ICT) among oil palm smallholders in Johor / Amirul Arif Ab Aziz - Ab Aziz, Amirul Arif (Faculty of Plantation and Agrotechnology, 2018)
Information and Communication Technologies (ICTs) play a vital role in the dissemination of agricultural information inputs for farmers to improve agriculutral productivity, gain better access to markets as well as achieve sustainable economic growth.Though efforts that was made to apply ICTs in the agricultural information sector, previous studies do not obviously reflect how ICTs impact to access and utilization of agricultural input information by farmers especially in Malaysia. To further understand this issue, the study aims to determine the level of accessibility of ICT and the factors that influence the level of ICT accessibility among oil palm smallholders. In this study, a random sampling was used to collect the data and the survey was conducted among oil palm smallholders in Johor. According to Krejcie and Morgan, the population is 150 samples size which indicates 108 respondents but only 85 respondents that involved this study. From the result obtained, it revealed that network factor and socio-economics such as age and educational level were the most significant factors that influenced the accessibility of ICTs among oil palm smallholders in Johor. Hence, the implementation of ICTs needs to be improved to increase the productivity of oil palm plantation in the future.